Translational Aspects of the Novel Object Recognition Task in Rats Abstinent Following Sub-Chronic Treatment with Phencyclidine (PCP): Effects of Modafinil and Relevance to Cognitive Deficits in Schizophrenia - Redrobe, John P.; Bull, Sascha; Plath, Niels (Frontiers in Psychiatry, 2010)
Phencyclidine (PCP) induces a behavioural syndrome in rodents that bears remarkable similarities to some of the core symptoms observed in schizophrenic patients, among those cognitive deficits. The successful alleviation of cognitive impairments associated with schizophrenia (CIAS) has become a major focus of research efforts as they remain largely untreated. The aim of the present study was to investigate the effects of selected antipsychotic and cognition enhancing drugs, namely haloperidol, risperidone, donepezil, and modafinil in an animal model widely used in preclinical schizophrenia research. To this end, the novel object recognition (NOR) task was applied to rats abstinent following sub-chronic treatment with PCP. Rats were administered either PCP (5 mg/kg, i.p.) or vehicle twice a day for 7 days, followed by a 7-day washout period, before testing in NOR. Upon testing, vehicle-treated rats successfully discriminated between novel and familiar objects, an effect abolished in rats that had previously been exposed to PCP-treatment. Acute treatment with modafinil (64 mg/kg, p.o.) ameliorated the PCP-induced deficit in novel object exploration, whereas haloperidol (0.1 mg/kg, s.c.), risperidone (0.2 mg/kg, i.p.) and donepezil (3 mg/kg, p.o.) were without significant effect. Given the negligible efficacy of haloperidol and risperidone, and the contradictory data with donepezil to treat CIAS in the clinic, together with the promising preliminary pro-cognitive effects of modafinil in certain subsets of schizophrenic patients, the sub-chronic PCP-NOR abstinence paradigm may represent an attractive option for the identification of potential novel treatments for CIAS.